Gender, true crime and criminology : offenders, victims and ethics - Wattis, Louise (Emerald studies in popular culture and gender., 2024)
Interest in true crime as a form of popular entertainment has sky-rocketed in recent years. Drawing on this current popularity and its significance in the context of digital culture, Gender, True Crime and Criminology challenges traditional definitions of the genre, expanding representations of victimhood and how we understand true crime audiences in gendered terms. Tackling male consumption of true crime and exploring texts which might appeal to men as consumers, Louise Wattis reveals a new opportunity to analyse representations of masculinity, class and violence, as well as how male audiences engage with cultural portrayals of these violent subjects. Embracing the breadth of the true crime genre, including features such as online engagement, sexual violence and the figure of the murdered woman, chapters critically analyse themes of gender, masculinity, race and class, as well as their representations in victim/survivor-centred documentaries. Situating wider debates within the renewed mainstream focus on violence against women, chapters also raise timely questions around ethics and the nature of victim visibility. Recognising the value of popular criminology as an academic resource, this is a much-needed text for advancing contemporaneous debates around the importance and diversity of true crime.